IMPACT OF BATCH-I (2009-10) PMKSY – WATERSHEDS PROGRAMME ON CROPPING PATTERN, CROP YIELDS AND HOUSEHOLD INCOME IN SRIKAKULAM DISTRICT OF ANDHRA PRADESH - P. RANJIT BASHA, M. SIVA PRASAD, S.V.N. RAO, D.V.S.R.L. REKHA* and B. MAHESH, (The Journal of Research ANGRAU, 2019)
The study mainly focused to assess the impact of the programme on incremental changes in croppingpattern, productivity and household income levels of Pradhan Mantri Krishi Sinchai Yojana (PMKSY) -Watershedsprojects of Srikakulam District. The programme has created a positive impact and could be attributed to the adoption ofsustainable development activities. Rice, maize, red gram, black gram, green gram are cultivated in kharif, whereas,vegetables, sesame and groundnut are grown during rabi seasons. In addition cashew, banana and mango are alsocultivated in large scale. Maize, red gram, black gram, green gram, vegetables, mango and cashew crops areashave been increased. Maize productivity has shown tremendous increase i.e. from 2866 kg ha-1 to 3578 kg ha-1,whereas, rice productivity increased from 3744 kg ha-1 to 4413 kg ha-1 during project period. Increase of productivityof maize is 25 % during kharif and 23% in rabi, whereas, in rice, 19 % in kharif and 21% in rabi. The productivity ofgreen gram increased from 321 kg ha-1 to 408 kg ha-1, an increase of 27% over the pre project period. Similarly, blackgram productivity increased from 326 kg ha-1 to 400 kg ha-1, an increase of 23% during the project period.Implementation of PMKSY-Watersheds has increased the number (31 No.) of higher income group households(>Rs.10,000 per month) indicating the beneficial effect of the program.*Corresponding author E-mail i.d: wapcoshydmeld@gmail.comJ.Res. ANGRAU 47(1) 57-63, 2019